The influence of coaches’ behavior on achievement motivation and performance of Riau athletes - Wijayanti, Ni Putu Nita; Tomoliyus; Abdul Alim; Wedi S; Wayan Artanayasa; Ketut Sudiana; Endang Rini Sukamti; Fauzi; Awan Hariono; Trisnar Adi Prabowo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to analyze and demonstrate the influence of coaches’ behavior on the motivation and performance of athletes. This correlational descriptive study utilized the Structural Equation Model (SEM) approach through the smart PLS analysis application. The study comprised a sample of 121 athletes from various individual and group sports. The behavior of coaches’, in general, encompasses five variables: mental skill, coaching style, character building, nutrition knowledge, and coaching science. Motivation comprises intrinsic and extrinsic factors, while athletes’ performance is determined by their qualities during training and physical test results. Data collection involved distributing questionnaires, supplemented by several interviews to bolster the research findings. The study’s findings illustrated the R-squared determinant coefficients, indicating the significance of trainer behavior in athletes’ performance, which stands at 0.696 (69.6%), and the impact of trainer behavior on motivation, recorded at 0.448 (44.8%). Among the variables tested, only one variable (character building) showed no discernible effect on athletes’ performance (p > 0.05). Conversely, the remaining variables significantly influenced achievement motivation, athletes’ performance, or mediated variables through achievement motivation to athlete performance (p < 0.05). These results are anticipated to serve as a guideline for coaches, emphasizing the pivotal role of coach quality in athletes’ technical performance and overall achievement.